1998
DOI: 10.1182/blood.v92.4.1219
|View full text |Cite
|
Sign up to set email alerts
|

The Distal Cytoplasmic Domain of the Erythropoietin Receptor Induces Granulocytic Differentiation in 32D Cells

Abstract: The role of hematopoietic growth factors in lineage commitment and differentiation is unclear. We present evidence that heterologous expression of an erythroid specific receptor allows granulocytic differentiation of a myeloid cell line. We have previously characterized a truncation mutant of the erythropoietin receptor (EpoR), which is associated with familial erythrocytosis (Blood89:4628, 1997). This truncated EpoR lacks the distal 70 amino acids of the cytoplasmic domain. To study the functional role of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Epo is a lineage‐specific cytokine that exerts its principal biologic effect on differentiating erythroid progenitor cells, associated with relatively restricted tissue expression of its specific cell surface Epo receptor (EpoR) (16–18). In previous studies we observed that ectopic expression of EpoR in myeloid 32D cells was associated with limited Epo‐induced myeloid differentiation (19). This observation suggested that the cellular environment in which a receptor functions, not receptor‐specific signals, determines the specificity of differentiation responses after cytokine receptor activation.…”
mentioning
confidence: 93%
“…Epo is a lineage‐specific cytokine that exerts its principal biologic effect on differentiating erythroid progenitor cells, associated with relatively restricted tissue expression of its specific cell surface Epo receptor (EpoR) (16–18). In previous studies we observed that ectopic expression of EpoR in myeloid 32D cells was associated with limited Epo‐induced myeloid differentiation (19). This observation suggested that the cellular environment in which a receptor functions, not receptor‐specific signals, determines the specificity of differentiation responses after cytokine receptor activation.…”
mentioning
confidence: 93%